A incidência do ISSQN nos serviços notariais e registrais - Oliveira, Magno Régio de (2023)
The present study addresses the incidence of the Tax on Services of Any Nature, as provided in the CRFB/88, in its art. 156, III, of the Federal Constitution and in the Complementary Law no. 116/2003, items 21 and 21.1, and the analysis of the Direct Action of Unconstitutionality no. 3.089-2, proposed by the Association of Notaries and Registrars. The foundation for the unconstitutionality is legally based on the violation of arts. 145, II, 156, III, and 236 of the Constitution of the Federative Republic of Brazil of 1988. The main question revolves around the current legal system of the Tax on Any Service Nature – ISSQN, regarding its incidence on public registry, notary, and registry services, and the decision of the Federal Supreme Court in the Direct Action of Unconstitutionality no. 3.089-2, filed by the Association of Notaries and Registrars of Brazil – ANOREG. Understanding this matter is pivotal in defining the legality of the taxation on such essential services for the population, with significant reflections in the social and legal reality. Given the controversies presented, the study aims to clarify the constitutionality or unconstitutionality of the ISSQN's incidence in this context. The employed methodology features an inductive method, applied nature, and descriptive purpose, as well as encompasses a qualitative analysis of judicial decisions, especially the arguments in the Direct Action of Unconstitutionality n. 3.089-2. In conclusion, based on the analysis of the votes from the ADI, the thesis defends the constitutionality of items 21 and 21.1, from the annexed list of Complementary Law n. 116/2003, that is, the incidence of ISSQN on notarial and registry services, since the ADI was found to be unfounded.